2011
DOI: 10.1593/neo.11652
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Expression of Oncogenic C-RAF in Mouse Pulmonary Epithelial Cells Reveals Differential Tumorigenesis and Induction of Autophagy Leading to Tumor Regression

Abstract: Here we describe a novel conditional mouse lung tumor model for investigation of the pathogenesis of human lung cancer. On the basis of the frequent involvement of the Ras-RAF-MEK-ERK signaling pathway in human non-small cell lung carcinoma (NSCLC), we have explored the target cell availability, reversibility, and cell type specificity of transformation by oncogenic C-RAF. Targeting expression to alveolar type II cells or to Clara cells, the two likely precursors of human NSCLC, revealed differential tumorigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…To start, we looked in the literature for experimentally validated miR-7-5p targets and then narrowed our research to the ones described to participate in the regulation of the autophagy process. The RAF1 kinase mRNA was an interesting candidate as it fulfilled these criteria both as a target of miR-7-5p, as described in melanoma cells [ 59 ], and as a regulator of autophagy, as previously reported [ 60 , 61 ].…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…To start, we looked in the literature for experimentally validated miR-7-5p targets and then narrowed our research to the ones described to participate in the regulation of the autophagy process. The RAF1 kinase mRNA was an interesting candidate as it fulfilled these criteria both as a target of miR-7-5p, as described in melanoma cells [ 59 ], and as a regulator of autophagy, as previously reported [ 60 , 61 ].…”
Section: Resultsmentioning
confidence: 63%
“…Of interest, an enhanced and detrimental autophagy was similarly observed following an ALKBH5 silencing/miR-7-5p increase and subsequent downregulation of the EGFR/Akt/mTOR axis in epithelial ovarian cancer cells [58]. In the literature, RAF1 inhibition was shown to induce autophagy and tumor regression in a conditional mouse model for RAF1-induced lung tumorigenesis [61]. Conversely, Kinsey et al recently demonstrated that the RAF1/MEK/ERK pathway inhibition elicited protective autophagy in pancreatic ductal adenocarcinoma cells, through the activation of the LKB1/AMPK/ULK1 signaling axis [83].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Autophagy is believed to have both pro‐ and anti‐oncogenic effects on tumor cells . Disrupted Beclin 1 in mice enhances the incidence of several types of cancers in mice, suggesting a suppressive role for autophagy , and autophagy inducers are widely used to kill cancer cells ; Evidence also suggests that autophagy plays a protective role in some cancer cells . Whether autophagy inducers suppress cancer cells may depend on the individual inducers used or the context of protein profiles within the cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although the three RAF proteins can phosphorylate ERK, B-RAF is the most efficient one, and therefore, it plays a central role in the physiopathology of cell proliferation [ 15 ]. The first Raf gene was isolated from retroviruses [ 16 ] and was found to be closely associated with cancer [ 17 ]. C-RAF is also ubiquitous [ 18 ] and plays a role in cell survival [ 19 ].…”
Section: Introductionmentioning
confidence: 99%